The Bacterial Microbiome of Meloidogyne-Based Disease Complex in Coffee and Tomato - Lamelas, Araceli; Desgarennes, Damaris; López-Lima, Daniel; Villain, Luc; Alonso-Sánchez, Alexandro; Artacho, Alejandro; Latorre, Amparo; Moya, Andrés; Carrión, Gloria (Frontiers in Plant Science, 2020)
The Meloidogyne-based disease complexes (MDCs) are caused by the interaction of different root-knot nematode species and phytopathogenic fungi. These complexes are devastating several important crops worldwide including tomato and coffee. Despite their relevance, little is known about the role of the bacterial communities in the MDCs. In this study 16s rDNA gene sequencing was used to analyze the bacterial microbiome associated with healthy and infested roots, as well with females and eggs of Meloidogyne enterolobii and M. paranaensis, the causal agents of MDC in tomato and coffee, respectively. Each MDC pathosystems displayed a specific taxonomic diversity and relative abundances constituting a very complex system. The main bacterial drivers of the MDC infection process were identified for both crops at order level. While corky-root coffee samples presented an enrichment of Bacillales and Burkholderiales, the corcky-root tomato samples presented an enrichment on Saprospirales, Chthoniobacterales, Alteromonadales, and Xanthomonadales. At genus level, Nocardia was common to both systems, and it could be related to the development of tumor symptoms by altering both nematode and plant systems. Furthermore, we predicted the healthy metabolic profile of the roots microbiome and a shift that may result in an increment of activity of central metabolism and the presence of pathogenic genes in both crops.